1 - Higher Education, the State and the Marketplace* - Mamdani, Mahmood (Journal of Higher Education in Africa, 2008)
This essay is an overview of the historical development of higher education through three different periods – colonial, nationalist and neoliberal – as well as an argu- ment for the strategic importance of higher education. In contrast to the World Bank’s attempt to marginalize higher education as an elitist preoccupation, it argues that higher education is where teachers are trained, where curricula are developed, where the range of leadership of an independent country is cultivated, and where research is located. In sum, higher education is where we develop the range of choices which make democracy meaningful in different spheres of life. Higher education is the strategic heart of education; those who wish to transform general education must begin with higher education. The essay closes with a critical discussion of two paradigmatic reform experiences in higher education in tropical Africa – developmentalist reform at the University of Dar-es-Salaam in the 1970s and market-based reform at Makerere University in the 1990s – so as to draw lessons from a half century of experience.